Knowledge of menstrual hygiene management among tribal menstruating females for the successful implementation of government policies in India - Mondal, Meghna; B. Saha, Kalyani; Dwivedi, Vijay K. (International Journal Of Community Medicine And Public Health, 2025)
Although the process of menstruation is a natural physiological process in women and is an indicator of good reproductive health, but due to the myths and stigmas associated with it, often it leads to misinformation, lack of awareness and hiding of management of the same. Lack of proper hygiene during menstruation can lead to increased vulnerability to problems like RTIs (reproductive tract infections) which significantly contribute to female morbidity. Therefore, there is a need to exercise menstrual hygiene management (MHM) by menstruating individuals.